YOUMARES 9 - The Oceans: Our Research, Our Future : Proceedings of the 2018 conference for YOUng MArine RESearcher in Oldenburg, Germany - Jungblut, Simon; Liebich, Viola; Bode-Dalby, Maya. (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access book summarizes peer-reviewed articles and the abstracts of oral and poster presentations given during the YOUMARES 9 conference which took place in Oldenburg, Germany, in September 2018. The aims of this book are to summarize state-of-the-art knowledge in marine sciences and to inspire scientists of all career stages in the development of further research. These conferences are organized by and for young marine researchers. Qualified early-career researchers, who moderated topical sessions during the conference, contributed literature reviews on specific topics within their research field. .
1. Science for the Future: The Use of Citizen Science in Marine Research and Conservation -- 2. A Literature Review on Stakeholder Participation in Coastal and Marine Fisheries -- 3. Law and Policy Dimensions of Ocean Governance -- 4. Status and Threats to Marine Biodiversity in the Anthropocene -- 5. Challenges in Marine Restoration Ecology: How Techniques, Assessment Metrics and Ecosystem Valuation can lead to Improved Restoration Success -- 6. Understanding how Microplastics Affect Marine Biota on the Cellular Level is Important for Assessing Ecosystem Function - A Review -- 7. Chemical Biodiversity and Bioactivities of Saponins in Echinodermata with an Emphasis on Sea Cucumbers (Holothuroidea) -- 8. Secondary Metabolites of Marine Microbes: From Natural Products Chemistry to Chemical Ecology -- 9. Sponges Revealed: A Synthesis of their Overlooked Ecological Functions within Aquatic Ecosystems -- 10. Theories, Vectors, and Computer Models - Marine Invasion Science in the Anthropocene -- 11. Benthos-Pelagos Interconnectivity: Antarctic Shelf Examples -- 12. Investigating the Land-Sea Transition Zone -- 13. Fisheries and Tourism: Social, Economic and Ecological Trade-offs in Coral Reef Systems -- 14. Progress in Microbial Ecology in Ice Covered Seas -- 15. Complex Interactions Between Aquatic Organisms and Their Chemical Environment Elucidated from Different Perspectives.
Springer Nature
Keywords: Biodiversity; Marine sciences; Fresh water; Aquatic ecology; Biotic communities; Wildlife; Fishes; Science -- Study and teaching; Biodiversity; Marine & Freshwater Sciences; Freshwater & Marine Ecology; Ecosystems; Fish & Wildlife Biology & Management; Science Education; Biodiversité.; Sciences de la mer; Eau douce; Poissons; Sciences -- Étude et enseignement; fresh water (water by property); Biotic communities; Aquatic ecology; Biodiversity; Fishes; Fresh water; Marine sciences; Science -- Study and teaching; Life sciences; Biodiversity; Marine sciences; Freshwater; Aquatic ecology; Ecosystems; Wildlife; Fish; Science education